Hydrogen Economy and Fuel Cells - George H Miley (Life At The Center Of The Energy Crisis: A Technologist's Search For A Black Swan, 2013)
My original undergraduate education was in Chemical Engineering with a minor in Physics, so it might seem natural for me to get into fuel cell research. However, having worked on nuclear energy for over 40 years, I had not been thinking about fuel cells or the hydrogen economy until recently. In 2004 a series of events occurred that changed this. Nie Luo, who had come to work with me as a post-doc on LENR research, brought up the subject in a discussion about cold fusion electrolytic cells. He had some thoughts about using energetic fuels like hydrogen peroxide and borohydride in a fuel cell. While the discussion was interesting, I had almost forgotten about it. Then one day Nie pointed out a DARPA SBIR request for proposals that included a topic on high powered fuel cells for military applications…